A case of Alice in Wonderland Syndrome associated with topiramate in a patient with vestibular migraine - Wen X. Jiang; Jonathan G. Leung, PharmD; Danielle N. Carlson, APRN, CNS-BC; Jeffrey P. Staab, MD, MS (Mental Health Clinician)
Introduction Alice in Wonderland Syndrome (AIWS) is an uncommon condition manifesting visual and somatosensory disturbances in which patients may perceive objects, including their own bodies, as larger or smaller than they are. In adults, AIWS typically is associated with migraine and epilepsy but has been reported as an adverse effect of topiramate, which is used to treat both illnesses, making it difficult to ascertain whether illness or medication causes altered perceptions. Reported is a case of topiramate-associated AIWS, which adds to the limited reports published on this unique phenomenon. Case Report A 40-year-old woman admitted to a 3-week pain rehabilitation program to treat chronic migraine reported macrosomatognosia that she retrospectively recalled beginning during titration of topiramate. The symptoms of AIWS resolved after the topiramate was discontinued. An assessment with the Naranjo ADR Probability Scale indicated a possible association between topiramate and macrosomatognosia. Discussion In this patient with migraine, the onset of AIWS coincided with titration of topiramate, providing a clue that its emergence may have been an adverse drug reaction rather than the underlying illness. Consistent with previous reports, AIWS resolved shortly after topiramate was discontinued, lending credence to this conclusion. However, the mechanism of AIWS is unknown and may be multifactorial, leaving the possibility that migraine predisposed the patient to develop AIWS from topiramate. Conclusion The long association of AIWS with migraine and epilepsy makes it possible that cases caused by medications used to treat these illnesses, like topiramate, are underreported. Awareness of the temporal relationships between the course of illness and the timing of drug therapy can help guide the recognition of AIWS as a potential adverse event.